Inducible Clindamycin-Resistant Staphylococcus aureus Strains in Africa: A Systematic Review - Assefa, Muluneh (International Journal of Microbiology, 2022)
Introduction. Excessive use of clindamycin enhances the acquisition of inducible clindamycin-resistant S. aureus strains, which is a significant health problem in Africa. The main objective of this review study was to determine the prevalence of inducible clindamycin resistance and related genes among S. aureus isolates in Africa. Methods. A qualitative systematic review was conducted on inducible clindamycin resistance among S. aureus isolates in Africa using electronic databases such as Google Scholar and PubMed. Articles published in English before 2021 were selected, and relevant data were extracted, collected, and analyzed. Results. In our search, 22 articles met the eligibility criteria for this review study. Of 3064 total S. aureus isolates, 605 had iMLSB phenotype. The overall prevalence of inducible clindamycin resistance in S. aureus isolates was 19.8% with a range of 2.9% to 44.0%. A high number of iMLSB phenotypes were observed in MRSA isolates (3.6–77.8%) than MSSA (0–58.8%). The overall prevalence of the iMLSB phenotype in MRSA strains was 26.8% (279/1041). The maximum peak prevalence of inducible clindamycin resistance among S. aureus isolates recorded in the continent was 44.0% in Egypt, followed by 35.8% in Libya and 33.3% in Uganda in 2017, 2007, and 2013, respectively. The highest prevalence of iMLSB phenotype in MRSA strains was reported in Egypt, 77.8%, followed by Nigeria, 75.0%, and Libya, 66.2%. Among the recovered drug-resistance genes, ermA, ermC, and msrA genes were commonly detected in Egypt with 67.9%, 70.0%, and 70.0% prevalence, respectively. Conclusion. This review highlights a higher inducible resistance of S. aureus, including MRSA strains to clindamycin in the continent. Regular screening of these strains, wise use of clindamycin, and molecular detection and genotyping of resistant genes are urgent.